External Support of Autologous Internal Jugular Vein Grafts with FRAME Mesh in a Porcine Carotid Artery Model - Chlupac, Jaroslav; Frank, Jan; Sedmera, David; Fabian, Ondrej; Simunkova, Zuzana; Mrazova, Iveta; Novak, Tomas; Vanourková, Zdenka; Benada, Oldrich; Pulda, Zdenek; Adla, Theodor; Kveton, Martin; et al. (Biomedicines, 2024)
BACKGROUND: Autologous vein grafts are widely used for bypass procedures in cardiovascular surgery. However, these grafts are susceptible to failure due to vein graft disease. Our study aimed to evaluate the impact of the latest-generation FRAME external support on vein graft remodeling in a preclinical model. METHODS: We performed autologous internal jugular vein interposition grafting in porcine carotid arteries for one month. Four grafts were supported with a FRAME mesh, while seven unsupported grafts served as controls. The conduits were examined through flowmetry, angiography, macroscopy, and microscopy. RESULTS: The one-month patency rate of FRAME-supported grafts was 100% (4/4), whereas that of unsupported controls was 43% (3/7, Log-rank p = 0.071). On explant angiography, FRAME grafts exhibited significantly more areas with no or mild stenosis (9/12) compared to control grafts (3/21, p = 0.0009). Blood flow at explantation was higher in the FRAME grafts (145 ± 51 mL/min) than in the controls (46 ± 85 mL/min, p = 0.066). Area and thickness of neo-intimal hyperplasia (NIH) at proximal anastomoses were similar for the FRAME and the control groups: 5.79 ± 1.38 versus 6.94 ± 1.10 mm2, respectively (p = 0.558) and 480 ± 95 vs. 587 ± 52 μm2/μm, respectively (p = 0.401). However, in the midgraft portions, the NIH area and thickness were significantly lower in the FRAME group than in the control group: 3.73 ± 0.64 vs. 6.27 ± 0.64 mm2, respectively (p = 0.022) and 258 ± 49 vs. 518 ± 36 μm2/μm, respectively (p = 0.0002). CONCLUSIONS: In our porcine model, the external mesh FRAME improved the patency of vein-to-carotid artery grafts and protected them from stenosis, particularly in the mid regions. The midgraft neo-intimal hyperplasia was two-fold thinner in the meshed grafts than in the controls.
Keywords: autologous vein graft; carotid artery; external stent; blood vessel prosthesis; pig